Financialized growth regime: lessons from Stock Flow Consistent models - Luis Reyes; Jacques Mazier (Revue de la Régulation)
The financialized growth rate that settled in most developed economies in the nineties is characterized by the quest for higher shareholders’ profitability, increased financial accumulation at the expense of productive accumulation and the use of leverage effects. Stock Flow Consistent models à la Godley and Lavoie are well suited to analyze this growth regime. We retain two types of closures for non financial companies, either an indebtedness norm or an own funds norm. The paper studies the dynamics of these two models with the aid of simulations and supply or demand shocks, or stemming from the financial sector. Their fitness to take into account financial cycles and over indebtedness typical of financialized growth may thus be analyzed. The model with the indebtedness norm generates short-term financial cycles which appear as the regulation mode of this growth regime with an asset price serving as an adjustment variable. The model with the own funds norm generates a financial bubble with growing indebtedness and no self-stabilizing mechanism.